2015
DOI: 10.1159/000430473
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting CD56+ and CD163+ Infiltrates in Early versus Late Renal Transplant Biopsies

Abstract: Background: CD56+ and CD163+ cell infiltration in human kidney transplant biopsies have not been fully evaluated. Methods: We investigated the association of CD56+ and CD163+ cell infiltration with human kidney transplant biopsies with antibody- or T-cell-mediated rejection (TCMR) and other histologic lesions. One hundred and seventy four clinically indicated transplant biopsies were included in this analysis. Immunohistochemical staining for C4d, CD56 and CD163 was performed. Results: One hundred and seventy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 26 publications
(26 reference statements)
1
25
0
1
Order By: Relevance
“…16 Intragraft NK cells (CD56 þ cells) in kidney transplant biopsy specimens have also been reported to be associated with interstitial fibrosis and poor clinical outcomes. 17,18 However, single staining for these antigens is not sufficiently specific to directly identify NK cells, given the broader expression of these markers in T-cell subpopulations. 19,20 Furthermore, expression of both CD57 and CD16 antigens within the NK cell compartment is primarily restricted to CD56 dim NK cells, highlighting an underrepresentation of markers identifying CD56 bright NK cells in these previous studies.…”
mentioning
confidence: 99%
“…16 Intragraft NK cells (CD56 þ cells) in kidney transplant biopsy specimens have also been reported to be associated with interstitial fibrosis and poor clinical outcomes. 17,18 However, single staining for these antigens is not sufficiently specific to directly identify NK cells, given the broader expression of these markers in T-cell subpopulations. 19,20 Furthermore, expression of both CD57 and CD16 antigens within the NK cell compartment is primarily restricted to CD56 dim NK cells, highlighting an underrepresentation of markers identifying CD56 bright NK cells in these previous studies.…”
mentioning
confidence: 99%
“…That can suggest a role of NK cells in the mechanism of microcirculation injury in acute rejections, more specifically in glomerular compartment. Hidalgo et al also studied biopsies from renal transplant by CD56 immunostaining and they observed higher number of CD56+ cells associated with peritubular capillaritis and Shin et al observed an increased number of CD56 + cells correlated with late biopsies, chronic active antibody‐mediated rejection and graft survival. None of those studies found associations between CD56+ infiltrate and glomerulitis.…”
Section: Discussionmentioning
confidence: 99%
“…These data support the different role of NK cells in ABMR compared to the TCMR. Shin et al also reported a positive correlation between the number of CD56 + cells and the severity of T cell-mediated rejection (63). In addition, it has been recently demonstrated that transcripts from activated NK cells are the only among those from leukocyte types that differentiate antibody-and T cell-mediated rejections and correlate with transplant outcome (55).…”
Section: Nk Cell Involvement In Acute and Chronic Allograft Rejectionmentioning
confidence: 97%